Well-Posedness and Uniform Decay Rates for a Nonlinear Damped Schrödinger-Type Equation - Cavalcanti Marcelo M.; Domingos Cavalcanti Valéria N. (Advanced Nonlinear Studies, 2021)
In this paper we study the existence as well as uniform decay rates of the energy associated with the nonlinear damped Schrödinger equation,